Bipolar Switching Properties and Reaction Decay Effect of BST Ferroelectric Thin Films for Applications in Resistance Random Access Memory Devices - Yao-Chin Wang; Kai-Huang Chen; Ming-Cheng Kao; Hsin-Chin Chen; Chien-Min Cheng; Hong-Xiang Huang; Kai-Chi Huang (Nanomaterials)
In this manuscript, strontium barium titanate (BST) ferroelectric memory film materials for applications in the feasibility of applying to non-volatile RAM devices were obtained and compared. Solutions were synthesized with a proportional ratio and through the deposition of BST films on titanium nitride/silicon substrates using the sol–gel method, using rapid thermal annealing for defect repair and re-crystallization processing. The crystallization structure and surface morphology of annealed and as-deposited BST films were obtained by XPS, XRD, and SEM measurements. Additionally, the ferroelectric and resistive switching properties for the memory window, the maximum capacitance, and the leakage current were examined for Al/BST/TiN and Cu/BST/TiN structure memory devices. In addition, the first-order reaction equation of the decay reaction behavior for the BST film RRAM devices in the reset state revealed that <semantics>r=0.19[O2−]1</semantics>. Finally, the Cu/BST/TiN and Al/BST/TiN structures of the ferroelectric BST films RRAM devices exhibited good memory window properties, bipolar switching properties, and non-volatile properties for applications in non-volatile memory devices.